G55(P) Audit on Optimal Positioning of Peripherally Inserted Central Catheters in Neonates. (4th June 2013) - Saha, A; Fernandez, R
Abstract : Aims: Changes in arm position has been known to cause migration of peripherally inserted central catheter (PICC) tips in neonates, however this relationship is poorly understood. An optimal placement of central catheter tip in neonates is essential to minimise life threatening complications like cardiac tamponade. This study aims to ascertain the relationship between arm position and central catheter tip displacement in neonates, with an aim to subsequently develop a clinical guideline on the optimal use of these lines by minimising catheter tip migration and its complications. Methods: After ethical approval was granted by the Education Department at the Deanery, an audit was undertaken at a tertiary neonatal unit to collect data on paired radiographs in order to establish the relationship between the angle of the arm at the shoulder and correlating it with the location of the catheter tip as seen on plain radiography. The angle of the arm with respect to the midline of the body was carefully measured, and the location of the tip of the PICC lines was identified using agreed bony reference points, and its distance from the heart was measured. Paired X-rays (of the same baby) were compared with careful documentation of the perceived changes PICC line tip positions with respect to different angles of arm position. Results: A total of 32 pairs of X-rays that met our criteria were reviewed. Arm movements were associated with catheter displacement. For catheters placed in the basilic vein, there was a mean displacement of 0.17mm/degree (–0.53 to +1.4) towards the heart on adduction and 0.1mm/degree (–0.46 to +0.4) away from the heart on abduction of the arm. Similarly, for the cephalic vein, there was a mean displacement of 0.34mm/degree (–0.53 to +1.6) towards the heart on adduction and 0.32mm/degree (–0.8 to +0.43) away from the heart on abduction of the arm. Conclusion: Although this study did not establish any correlation in magnitude or direction, a clinically significant degree of catheter tip migration was observed with changes in arm position for each paired radiograph reviewed. A further prospective study under direct ultrasound visualisation is envisaged to study this relationship further.